Motivation to Use Artificial Intelligence and Technology Self-Efficacy among Biology Education Students at an Indonesian University - Rizka, Chairany (Aspirasi Masyarakat Intelektual Islam Nusantara, 2025)
The rapid integration of artificial intelligence (AI) in higher education requires students to possess both strong motivation and sufficient technological confidence to use AI effectively for learning. This study investigates the relationship between motivation to use artificial intelligence and technology self-efficacy among Biology Education students at an Indonesian university. A mixed-methods survey design was employed involving 62 undergraduate students. Quantitative data were collected using two validated Likert-scale questionnaires measuring motivation to use AI and technology self-efficacy, while qualitative data were obtained through open-ended questions addressing students’ perceived benefits and limitations of AI in learning. Descriptive analysis showed that students reported high motivation to use AI (mean scores across expectancy–value dimensions ranged from 3.46 to 3.90) and moderate to high technology self-efficacy (mean scores ranged from 3.51 to 3.85), with the highest level observed in AI-specific self-efficacy (M = 3.85). Pearson correlation analysis revealed a significant positive relationship between motivation to use AI and technology self-efficacy (p = 0.001). Qualitative findings indicated that students perceived AI as enhancing learning efficiency, conceptual understanding, and independent learning, while also expressing concerns related to accuracy, overdependence, and ethical issues. These findings highlight the importance of pedagogically guided and ethically informed AI integration in teacher education programs.